A Thirty-Year Follow-Up Surveillance Study for Neoplasia of a Dutch Ulcerative Colitis Cohort - J. A. M. Stolwijk; A. M. J. Langers; J. C. Hardwick; R. A. Veenendaal; H. W. Verspaget; R. A. van Hogezand; H. F. Vasen; A. E. van der Meulen-de Jong (The Scientific World Journal)
Background. Patients with ulcerative colitis have an increased risk of developing colorectal cancer (CRC). The aim of this study is to assess the yield of surveillance colonoscopies in a tertiary referral cohort of ulcerative colitis patients and to identify different risk groups for dysplasia. Methods. A cohort of 293 patients (148 males, mean age 33.8 years at diagnosis) was built up at our center and started the surveillance program 8–12 years after start of symptoms. They underwent colonoscopies every one to three years. Endpoints were dysplasia or a (sub)total colectomy. Results. After a follow-up period of 10 years, the cumulative incidence of any dysplasia was 23.5%, and of CRC 4.0%. After 15 years these percentages were 33.3% and 6.8%. Patients with pancolitis (n=178) had a significantly higher cumulative risk of dysplasia than patients with distal disease, HR 1.9 (95%CI 1.1–3.3). Patients who started surveillance at an older age are at increased risk for any dysplasia, HR 1.03 (95%CI 1.01–1.05). Conclusions. This prospective surveillance study shows a high yield of dysplasia in ulcerative colitis patients. We recommend developing separate surveillance programs for different risk groups. In our opinion patients with distal colitis can follow the general population surveillance program.